2022
DOI: 10.3389/fonc.2022.941496
|View full text |Cite
|
Sign up to set email alerts
|

Body composition change during neoadjuvant chemotherapy for breast cancer

Abstract: BackgroundSarcopenia is receiving attention in oncology as a predictor of increased chemotherapy toxicities. Research into body composition change during neoadjuvant chemotherapy for breast cancer is both urgently needed and generally lacking. This study assessed sarcopenia prevalence before and after neoadjuvant chemotherapy using CT imaging, evaluated body composition changes during neoadjuvant chemotherapy, and determined predictors of sarcopenia status after neoadjuvant chemotherapy for breast cancer.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This serial biopsy approach allowed the investigators to record changes in mitochondrial biogenesis, mitochondrial dynamics and mitophagy [49 ▪▪ ] as well as fatty infiltration [50], specific to a treatment plan that includes anthracycline, cyclophosphamide and taxane. Although muscle mass loss was undetectable by CT when patients received this regimen [12,13 ▪ ,14] (see above), microscopic and biochemical tests reveal important changes.…”
Section: Molecular Pathways Of Systemic Treatment-related Muscle Lossmentioning
confidence: 97%
See 1 more Smart Citation
“…This serial biopsy approach allowed the investigators to record changes in mitochondrial biogenesis, mitochondrial dynamics and mitophagy [49 ▪▪ ] as well as fatty infiltration [50], specific to a treatment plan that includes anthracycline, cyclophosphamide and taxane. Although muscle mass loss was undetectable by CT when patients received this regimen [12,13 ▪ ,14] (see above), microscopic and biochemical tests reveal important changes.…”
Section: Molecular Pathways Of Systemic Treatment-related Muscle Lossmentioning
confidence: 97%
“…Significant loss of skeletal muscle was observed in all investigated disease sites, settings and regimens (range À3.8 to À13.7%/100 days), with the exception of neoadjuvant chemotherapy for breast cancer (regimens including anthracycline/cyclophosphamide/taxane) in three studies, which were uniformly negative for muscle loss [11,12,13 ]. This is perhaps unsurprising, as weight gain not weight loss is associated with this treatment.…”
Section: Muscle Lossmentioning
confidence: 99%
“…These results concur with our previous study in which we monitored 70 patients with breast cancer for 6 months and reported a significant reduction in muscle mass and an increase in fat mass at 6 months when there was no exercise intervention. Many patients with breast cancer who receive chemoradiation therapy experienced changes in body composition . Our intervention led to minimal changes in body composition in the exercise group despite no additional intervention after 1 month.…”
Section: Discussionmentioning
confidence: 86%
“…Axillary web syndrome 0 tients with breast cancer who receive chemoradiation therapy experienced changes in body composition. [46][47][48] Our intervention led to minimal changes in body composition in the exercise group despite no additional intervention after 1 month. Based on our findings, we can speculate that providing exercise rehabilitation would reduce medical expenses and lower the economic burden on the health care system.…”
Section: Discussionmentioning
confidence: 99%
“…It has shown notable efficacy in enhancing event-free survival (EFS) and overall survival (OS) rates, particularly among patients who achieve pathological complete response (pCR) during treatment ( 6 8 ). Additionally, the customization of post-neoadjuvant treatments has been promising in augmenting long-term outcomes for patients who do not attain pCR ( 9 , 10 ). This underscores the importance of accurately predicting pCR in breast cancer patients, a critical factor in optimizing treatment strategies and improving survival prospects.…”
Section: Introductionmentioning
confidence: 99%